2016
DOI: 10.1002/2016ja023105
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework for the changing spectral properties of meter‐scale Farley‐Buneman waves between 90 and 125 km altitudes

Abstract: Stimulated by recent observations described in a companion paper, we have revisited existing theories of the Farley‐Buneman instability throughout the altitude range 90 to 125 km. We have assumed that the irregularities detected by radars at a given altitude are dominated by structures moving at the threshold speed in a direction associated with maximum linear growth rate conditions. We included recent nonisothermal electron and ion theories, which can modify threshold speeds by considerable amounts. We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…In northern Germany, the 17 March 2015 storm also led to the occurrence of E region ionospheric irregularities (50–80 km size) of narrow spectral width with both low and high Doppler speeds corresponding to different parts of the E region [ Chau and St.‐Maurice , ]. St.‐Maurice and Chau [] suggested that Farley‐Buneman instability with nonthermal electrons and ions was the source of the irregularities. Subauroral and midlatitude processes . Many subauroral processes having potential mesoscale or even global impacts are closely related to those at high latitudes and magnetosphere‐ionosphere coupling.…”
Section: Main Results: Geospace Responses To the St Patrick's Day Stmentioning
confidence: 99%
“…In northern Germany, the 17 March 2015 storm also led to the occurrence of E region ionospheric irregularities (50–80 km size) of narrow spectral width with both low and high Doppler speeds corresponding to different parts of the E region [ Chau and St.‐Maurice , ]. St.‐Maurice and Chau [] suggested that Farley‐Buneman instability with nonthermal electrons and ions was the source of the irregularities. Subauroral and midlatitude processes . Many subauroral processes having potential mesoscale or even global impacts are closely related to those at high latitudes and magnetosphere‐ionosphere coupling.…”
Section: Main Results: Geospace Responses To the St Patrick's Day Stmentioning
confidence: 99%
“…It was from this setup that the notion that Type III and Type IV echoes came from the lowest and highest altitudes of the unstable layer was developed. This, and the very narrow spectral widths of the scatter, triggered new theoretical ideas about the origin of these spectral types by St.-Maurice and Chau (2016).…”
Section: 1029/2018rs006747mentioning
confidence: 99%
“…These publications describe and characterize the different types of radar echoes received from the ionospheric E region of the Earth and the technical progress that has taken place over the years. Recent progress has been made by St.‐Maurice and Chau () with regard to the generation and propagation of the plasma density irregularities in the E region. Some of these findings include the following: (1) The Doppler shifts observed close to the ion‐acoustic speed in the vicinity of the E × B direction (so‐called Type I) are from plasma density irregularities in the middle of the E region (near 110 km) because they are associated with the zero growth rates that the structures have when they reach their maximum amplitude; (2) the spectra with broad Doppler width and slow Doppler shifts in the vicinity of the electric field direction (so‐called Type II) come from the fact that the structures are not plane waves but, instead, have a finite size along the electric field direction; (3) the narrow slow and narrow fast spectra (so‐called Types III and IV) come from weakly growing structures at the top and the bottom of the E region plasma layer.…”
Section: Introductionmentioning
confidence: 99%
“…Here v n corresponds to the neutral wind speed in the line of sight (LOS) of the radar, θ to the angle between the electron drift velocity and the radar wave vector, and θ 0 to an offset representing wave turning due to thermal effects (St. Maurice & Chau, ). Also, α is a value related to the state parameters of the system (Hysell et al, ).…”
Section: Estimation Of Flows From Spectral Datamentioning
confidence: 99%
“…Their results predict that the Doppler shift and spectral width of coherent scatter of Farley‐Buneman waves are approximately proportional to the product of the ion acoustic speed ( c s ) with the cosine of the flow angle ( θ ) and the product of the ion acoustic speed with the sine of the flow angle, respectively. Thermal effects cause the simulated waves to propagate in a direction slightly different from the electron convection velocity ( v d ; St. Maurice & Chau, ). Also, Oppenheim and Dimant's simulations show that the ion acoustic speed increases with the convection electric field due to wave heating and thermal effects in a predictable way.…”
Section: Introductionmentioning
confidence: 99%